2022
DOI: 10.1101/2022.04.01.486487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivoprenylomic profiling in the brain of a transgenic mouse model of Alzheimer’s disease reveals increased prenylation of a key set of proteins

Abstract: Dysregulation of protein prenylation has been implicated in many diseases, including Alzheimer's disease (AD). Prenylomic analysis, the combination of metabolic incorporation of an isoprenoid analogue (C15AlkOPP) into prenylated proteins with a bottom-up proteomic analysis, has allowed identification of prenylated proteins in various cellular models. Here, transgenic AD mice were administered with C15AlkOPP through intracerebroventricular (ICV) infusion over 13 days. Using prenylomic analysis, 36 prenylated pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…In previous work, 15,16 we observed a correlation between transcript level and enrichment of prenylated proteins obtained via the procedure described above, suggesting that protein abundance is one of the factors that controls what prenylated proteins can be detected using this chemical proteomic workflow. Accordingly, when the fold change of shared proteins in the ESderived motor neurons was compared to the relative transcript counts from previously reported transcriptomic work, 22 a statistically significant positive correlation was observed (Figure S9).…”
Section: Proteomic Analysis Of Es Astrocytes Es Motor Neurons and Esc...mentioning
confidence: 69%
See 1 more Smart Citation
“…In previous work, 15,16 we observed a correlation between transcript level and enrichment of prenylated proteins obtained via the procedure described above, suggesting that protein abundance is one of the factors that controls what prenylated proteins can be detected using this chemical proteomic workflow. Accordingly, when the fold change of shared proteins in the ESderived motor neurons was compared to the relative transcript counts from previously reported transcriptomic work, 22 a statistically significant positive correlation was observed (Figure S9).…”
Section: Proteomic Analysis Of Es Astrocytes Es Motor Neurons and Esc...mentioning
confidence: 69%
“…15 Those studies also showed that such experiments could simultaneously monitor changes in the prenylation of all observable prenylated proteins that occur upon treatment with various pharmacological agents. Recently, we reported the use of this metabolic labeling approach in vivo, in a mouse animal model for Alzheimer's disease, to study the dysregulation of protein prenylation in that disease 16 and to study the impact of knock-down of a newly identified putative deprenylating enzyme. 17 In work reported by Li et al, it was shown that inhibitors of protein prenylation can serve as potent neurite-outgrowth-promoting agents.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we recently identified ALDH9A1 as a protein with increased levels of prenylation in Alzheimer's disease. 49 Since prenylation of ALDH9A1 on the catalytic residue Cys288 must inhibit its activity, this observation may provide a link between oxidative stress, neuroinflammation and Alzheimer's disease. 50…”
Section: The Isoprenoid Modification Is Hydrolyzablementioning
confidence: 99%